Exposure to nicotine vapor in male adolescent rats produces a withdrawal-like state and facilitates nicotine self-administration during adulthood - Kallupi, Marsida (Eur Neuropsychopharmacol, 2019)
Electronic cigarette use is particularly prevalent in adolescents, but the effects of secondhand exposure to nicotine vapor in adolescents on the propensity to develop nicotine dependence and increase nicotine self-administration in adulthood are poorly known. The present study explored the effects of nicotine vapor exposure on withdrawal-like states (hyperalgesia, spontaneous withdrawal signs, and locomotor activity) in adolescent rats and the vulnerability to acquire intravenous nicotine self-administration in adulthood. Adolescent (postnatal day 38) rats were exposed to intermittent nicotine vapor (14 h/day) for 7 consecutive days in a range of doses (0, 0.4, and 7 mg/m(3)). The rats were tested for somatic, emotional, and motivational withdrawal symptoms. When the animals reached adulthood, they were allowed to self-administer nicotine (0.03 mg/kg/0.1 ml) intravenously in operant chambers for 1 h/day for 12 consecutive days. Rats that were exposed to nicotine vapor presented moderate to severe signs of spontaneous withdrawal after the cessation of nicotine vapor. No effect on anxiety-like behavior was observed. Rats that were exposed to high levels of nicotine vapor in adolescence had lower pain thresholds and exhibited faster and higher acquisition of nicotine self-administration in adulthood. Chronic exposure to nicotine vapor in adolescent rats produces a withdrawal-like state and facilitates the acquisition of intravenous nicotine self-administration in adulthood. These results suggest that exposure of adolescents to nicotine vapor may confer higher risk of developing nicotine dependence when they become adults.